The study of the graph of exponential functions from the theory of Raymond Duval (Research, Society and Development, 2022)
Based on the Theory of Registers of Semiotic Representation by Raymond Duval, this research aims to present a study of the sketch of curves of exponential functions starting from the approach of the global interpretation of figural properties. This approach allows a broader look at the function curves compared to the point-to-point approach, since it only considers some specific points of the curve, thus, they end up limiting the interpretation in its entirety. The global interpretation of figural properties establishes correspondences between algebraic and graphic representations, favoring the conversion in the double sense. This is a research with a qualitative approach and bibliographic nature. In view of the above, we conclude that considering the figural properties of the curve makes it possible to visualize it as a whole, allowing the conversion between algebraic and graphical representations to occur in both directions. Note also the use of translation and symmetry as resources allowed the sketch of more complex curves.